Two Discrete cis Elements Control the Abaxial Side–Specific Expression of the FILAMENTOUS FLOWER Gene in Arabidopsis - Watanabe, Keiro (American Society of Plant Biologists, 2003)
Our previous studies showed that a member of the YABBY gene family, FILAMENTOUS FLOWER (FIL), plays a role in specifying the abaxial side tissues in the development of lateral organs such as cotyledons, leaves, young flower buds, and flower organs. We examined the expression pattern of FIL and found a temporal change of expression domains in the developmental process of the floral meristem. We also examined the cis control regions by constructing a series of transgenic plants that carry green fluorescent protein under the control of the FIL promoter with several types of deletions, base changes, and tandem repeats and showed that the unique expression pattern is dependent on at least two cis-acting elements in the 5′ regulatory region. One element proximal to the FIL gene would be responsible for the expression of both the abaxial and adaxial sides, and the other element of the 12-bp sequence would work to repress expression on the adaxial side.